Elastoplastic modeling of fatigue cracks - K. A. Vansovich; V. I. Yadrov (Омский научный вестник)
The presented work provides a detailed analysis of modern approaches to creating elastoplastic models of surface crack growth that take into account the influence of the type of biaxial loading on the development of stresses and strains at the crack tip and, accordingly, on the crack growth rate. The use of the plastic stress intensity factor as a characteristic of resistance to cyclic deformation and fracture for biaxial loading conditions is substantiated. Continuum plasticity models are proposed to simulate the elastoplastic behavior of metal using numerical methods and, in particular, the finite element method.